A Comparative Study of High and Low Anxious Adolescents with Regard to Their Self-Handicapping Behaviour - Dr. Sarita Sharma; Dr. Vandana Sharma (International Journal of Indian Psychȯlogy, 2022)
Jones and Berglas in 1978 used the term “self-handicapping” to describe the situation when people feel uncertain about their performance, they tend to reduce their effort, so that blame for not performing well would go to not putting enough efforts instead of their ability. In this way they externalize their failure to protect their self. In the present study an effort was made to compare the high and low anxious peoples with regard to their level of self- handicapping behaviour. It was hypothesized that both the groups will differ significantly in terms of their level of self- handicapping. The sample of present study consisted of 300 students of class XI studying in different C.B.S.E Schools located in Meerut city, India. A State-Trait Anxiety Inventory constructed and standardized by Dr. Roma Pal and Govind Tiwari was used to measure the level of anxiety among students and to measure self-handicapping, a scale was prepared by the researcher, based on Rhodwalt’s self-handicapping scale. On the basis of scores on State-Trait Anxiety Inventory, students were divided into two groups i.e., high anxiety and low anxiety group with the help of calculated median value. Result showed that both the groups significantly differ with regard to their level of self-handicapping behaviour. It was observed that high state and trait anxiety groups have scored significantly higher on self-handicapping (p<.01) in comparison to low state and trait anxiety groups. To conclude, it can be said that the result of the present study indicates a significant effect of anxiety on self- handicapping behavior whether related to a specific situation or experienced in a generalized manner as high anxious students reported high self- handicapping in comparison to low anxious students.